Theoretical and experimental approach to ball bearing frictional characteristics compared with cryogenic friction model and dry friction model. (1st June 2019) - Kwak, Wonil; Lee, Jeonkook; Lee, Yong-Bok
Highlights: A cryogenic friction model for ball bearing dynamic analysis is shown. The hydrodynamic effect of cryogenic fluids is considered in the model. A dynamic experiment and cryogenic ball bearing analysis are performed. The proposed model yields a more accurate prediction than the dry friction model. Abstract: In previous studies on cryogenic ball bearings, a friction model of solid lubrication characteristics was employed with the assumption that the low dynamic viscosity of cryogenic fluids is negligible. A traction curve was then created using this dry friction model, with curve fitting being performed using a traction coefficient derived from the results of a ball-on-disk experiment with corresponding solid lubricant. However, the behavior prediction had many limitations, because the fluid characteristics in the cryogenic environment and the friction characteristics of the bearing components were not reflected. This study attempts to improve the reliability of cryogenic ball bearing dynamic analysis by proposing a hydrodynamic friction model considering the hydrodynamic effect of cryogenic fluids. A ball-on-disk experiment is conducted by simulating (1) ball-cage friction, (2) ball-inner/outer race friction, and (3) cage-inner/outer race friction characteristics. Hence, it is found that uncertainty factors causing traction coefficient fluctuation exist in certain device sections, reflecting the effect on the wear surface of friction and the hydrodynamic effect of the shear stress of the cryogenic fluid (liquid nitrogen). A dynamic experiment and cryogenic ball bearing analysis using the model considering the hydrodynamic effect are conducted and compared. From the ball bearing dynamic behavior analysis, the hydrodynamic friction model is found to predict a bearing friction coefficient that is closer to the actual value than the dry friction model. When the proposed model is applied to bearing dynamic behavior, it is possible to predict the cryogenic-bearing friction coefficient with 50% higher accuracy than the existing method.